Abuse of Discretionary Powers in Pakistan: Legal Loopholes, Institutional Weaknesses, and the Crisis of Accountability - Muhammad Sahil Khan; Dr. Tansif Ur Rehman; Aliya Saeed (Indus Journal of Social Sciences, 2025)
This paper explores the misuse of discretionary powers in Pakistan, as discretionary powers lead to arbitrariness, injustice, and loss of confidence by people in the institutions of the state. The paper considers legal omissions and judicial pronouncements and administrative practices that enable this abuse through the use of doctrinal and empirical approaches. A disturbing trend in the literature regards an unchecked discretion, particularly in the field of law enforcement, revenues, and the issue of license issuance. It largely results in selective policing and violation of constitutional rights. The lack of effective accountability procedures and a weak judicial oversight is explained as one of the key enablers of this type of abuse in the study. The article proposes practical changes to enhance transparency, justice, and juridical predictability. The solutions are based on case studies, legal framework analysis, and the comparison with international models. Finally, the reform of discretionary powers is of vital importance to unravel the constitutional balance and to keep in line the rights and rule of law in Pakistan.